The Influence of the Technology Acceptance Model (TAM) Dimensions on Interest in Using the OVO Application among Andalas University Students: Pengaruh Dimensi Technology Acceptance Model (TAM) Terhadap Minat Menggunakan Aplikasi OVO Pada Mahasiswa Universitas Andalas - Septri Dewi, Intan; Leni, Puspa; Mulya, Jumiatul (International Journal of Management and Business (IJMB), 2024)
The purpose of this research is to analyze the effect of the dimensions of the technology acceptance model (TAM) on intention to use the OVO application. This study uses a type of quantitative research with an associative design. The number of samples was 96 Andalas University students. The technique of Data analysis was using multiple linear regression analysis. The results of the study show that perceived usefulness and perceived ease of use partially had a positive and significant effect on intention to use the OVO application in the Andalas University students. Perceived security has no significant effect on interest in using the OVO application in Andalas University students. Based on the F test, perceived usefulness, perceived ease of use and perceived security simultaneously or together have a positive and significant effect on interest in using the OVO application at Andalas University students. Thus it can be concluded that it is important for the OVO company to increase perceived usefulness, perceived ease of use and perceived security to increase intention to use the OVO application.